a) (-3) la puterea 87 : (-3) la puterea 85 =(-3) la puterea (87-85)=(-3)²
[(-3)² - (-3) la puterea 87 : (-3) la puterea 85 ] : 5 =[(-3)²-(-3)²]:5=(9-9):5=0
b) asa am inteles din ce ai scris
[(-2)²la puterea 95]²=(-2) la puterea (2*95*2)=2 la put.380=2² * 2 la put 378
{(-2)² + [(-2)²]la puterea 95]² } : 8 = (2²+2² * 2 la put 378):2³=(1+2 la put. 378)/2
c) (-4)la puterea 73 : 2 la 144= - (2²)la put.73 : 2 la 144= - 2 la put (2*73-144)= - 2²= -4
25 la puterea 12 : 5 la puterea 23=(5²)la put.12 : 5 la put. 23= 5 la put (2*12-23)=5
(-4)la puterea 73 : 2 la 144 - 25 la puterea 12 : 5 la puterea 23 = -4-5=-9